Implant-supported rehabilitation in edentulous patient with jaw atrophic. Case report - Alayo Silva, Ivonne (2017)
One of the challenges of dentistry is oral rehabilitation in totally edentulous patients with atrophic jaws. This case reports a protocol for implant treatment performed in elderly patient with an edentulous jaws and advanced atrophy, in which an implant-retained implant-supported and consistent rehabilitation was conducted in a superior hybrid prosthesis supported by 6 implants and on lower denture retained by a horizontal bar attached to 4 implants, with a total follow-up of 1 year, without reporting complications. This case gives us evidence of an implant and rehabilitation protocol for patients with severe atrophy thus improving poor retention and stability posed by conventional prostheses in atrophic jaws, and show the benefits in terms of masticatory efficiency and better quality of life for patients with this diagnosis.